The Parallel March of Asthma and Allergy in Childhood: A Multi-Perspective Approach - Carlo Caffarelli (Frontiers Research Topics, 2018)
It has not been yet clarified whether allergy and asthma are part of the same condition or they follow a parallel path. This Research Topic aims to try and put some light in this parallel march going through crucial topics: from prenatal events to later risk factors such as obesity; and from basic immunology to immunotherapy, both subcutaneous and sublingual. We hope the readers can infer their own conclusions as what is first: egg or chicken.